Scientific Rigor Level of Master’s Thesis in Education - Case Study: Public University - Benavente Flores, Mariana (2017)
This paper summarizes the main findings of an exploratory research (qualitative and quantitative) on street children and adolescents in the Province of Lima, Peru. This research aimed to have deeper knowledge about the environments (family and school) of children and adolescents before they started to live on the streets. Moreover, this research explored the reality that children and teenagers face once they start to live on the streets. This research also comprised the children’s expectations about the future, which, far from being fatalistic, were full of hope and desire for vindication.